1999
DOI: 10.1034/j.1398-9995.1999.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive capacity of histamine release for the diagnosis of drug allergy

Abstract: The usefulness of the in vitro histamine-release test for the diagnosis of drug allergy appears to be insufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 22 publications
(15 reference statements)
2
45
0
Order By: Relevance
“…This is in contrast with the clinical relevance of the phenomenon, considering the estimated high percentage (>77%) of non-IgE-mediated reactions among all hypersensitivity reactions (HSRs) to drugs (Demoly et al, 1999). These pseudoallergic reactions afflict, according to different statistics, up to 500 thousands patients every year in the USA (Lazarou et al, 1998;Adkinson et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…This is in contrast with the clinical relevance of the phenomenon, considering the estimated high percentage (>77%) of non-IgE-mediated reactions among all hypersensitivity reactions (HSRs) to drugs (Demoly et al, 1999). These pseudoallergic reactions afflict, according to different statistics, up to 500 thousands patients every year in the USA (Lazarou et al, 1998;Adkinson et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…It has been suggested that two-thirds of HSRs may be attributable to pseudoallergy [9]. Due to the lack of systematic studies of the causes and mechanisms involved in pseudoallergy, the diagnosis and treatment of these reactions remain a significant clinical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…application of certain nanoparticlecontaining medicines. [1][2][3] Premedication with steroids and other anti-allergic medicines can reduce the risk and severity of such adverse reactions; however, prevention by inhibiting the triggering mechanisms, e.g. complement activation, is expected to offer more specific and effective measure against this adverse immune effect.…”
Section: Introductionmentioning
confidence: 99%